Increased monocyte abundance as a marker for relapse after discontinuation of biologics in inflammatory bowel disease with deep remission - Kwon, Yiyoung; Kim, Yoon Zi; Choe, Yon Ho; Kim, Mi Jin (Frontiers in Immunology, 2022)
Monocytes are involved in the upstream inflammatory process in the immune reaction in 21 inflammatory bowel disease (IBD). Patients with IBD who discontinued biologics have been 22 found to relapse, even after checking for deep remission. This study investigated whether 23 monocytes could act as a predictor of relapse in patients who experienced relapse after the 24 discontinuation of biologics. To this end, pediatric patients (<19 years old, n = 727) diagnosed 25 with IBD from January 2003 to December 2021 were retrospectively reviewed. Clinical 26 features, monocytes, and disease activity at the time of discontinuing biologics were evaluated 27 by dividing patients into a relapsed group and a non-relapsed group after discontinuing 28 biologics. The percentage of monocytes (8.65% vs. 6.42%, P < 0.001), the absolute monocyte 29 count (614.79 cells/μL vs. 381.70 cells/μL, P < 0.001), and the monocyte/polymorphonuclear 30 leukocyte (PMN) ratio (0.18 vs. 0.11, P < 0.001) at the time of discontinuation were 31 significantly higher in patients who experienced relapse. As a result of multivariate analysis, 32 the monocyte percentage (odds ratio: 2.012, P < 0.001) and monocyte/PMN ratio (odds ratio: 33 4.320E+14, P = 0.002) were evaluated as risk factors for relapse. Diagnostic capability was 34 confirmed using area under operating characteristic curve (0.782) of the monocyte percentage 35 for assessing the relapse within 6 months with cutoff value of 8.15% (P < 0.001). The findings 36 presented in this study indicate that the patients with high monocyte counts experienced relapse 37 after the discontinuation of biologics. A monocyte percentage of over 8.15% in the blood at the 38 time of discontinuation was found to be associated with a high probability of relapse within 6 39 months, even in deep remission.